2017
DOI: 10.15406/acp.2017.02.00039
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features of Tubercular Lymphadenitis in HIV Positive Patients

Abstract: ResultsIn the current study, 33 cases (44%) were diagnosed as tubercular lymphadenitis and were the second most common causes of lymphadenopathy after reactive hyperplasia. The presenting complaints in this group were fever (100%) followed by cough (84%) and weight loss (75%). Generalized lymphadenopathy was seen in 25 cases (75.6%) where as cervical lymphadenopathy was found in 7 cases (21.2%). One case presented with axillary lymphadenopathy. All the patients (33) were clinically diagnosed as AIDS. A raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Jayalakshmi et al [8] reported epithelioid cell granulomas in 100% of cases with central caseation necrosis in 96.6% of cases. Agarwal et al [9] reported caseous necrosis as the most prominent feature in lymph node biopsies even in the absence of granulomas or in the presence of poorly formed ones in LNTB patients present with human immunodeficiency virus (HIV) infection. We also reported caseation necrosis as a primary finding in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Jayalakshmi et al [8] reported epithelioid cell granulomas in 100% of cases with central caseation necrosis in 96.6% of cases. Agarwal et al [9] reported caseous necrosis as the most prominent feature in lymph node biopsies even in the absence of granulomas or in the presence of poorly formed ones in LNTB patients present with human immunodeficiency virus (HIV) infection. We also reported caseation necrosis as a primary finding in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Lymph node TB is the most common extrapulmonary TB form in the immunosuppressed individuals including PLWH. It represents 16–30% of extrapulmonary tuberculosis cases [ 55 , 56 , 57 ], and >40% TB cases in PLWH [ 58 ]. In our study, the number of cases of lymph node TB was significantly lower (8,6% of the cases; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…GU TB commonly affects kidneys as well as the genital tract [ 63 ]. HIV/AIDS increases the risk to develop GU TB [ 58 ]. In our study, we found GU TB in only one patient.…”
Section: Discussionmentioning
confidence: 99%